Economic Efficiency Through Digital Transformation: A Strategic Approach to Multipurpose Loan Products - Dolitua, Arjuna; Wandebori, Harimukti (International Journal of Economics Development Research (IJEDR), 2025)
In response to rapid technological advancements in the financial sector, PT. XYZ Finance—a conventional non-bank financial institution—is facing increasing competitive pressure, particularly from the rise of digital financial services (fintech) in Indonesia. One of the most competitive products in this landscape is the multipurpose loan. According to the Financial Services Authority (OJK), outstanding multipurpose loans reached IDR 74.48 trillion as of September 2024, marking a year-on-year growth of 33.73%. This study aims to identify the root causes behind the slow adoption of digital transformation for multipurpose loan products at PT. XYZ Finance and to formulate appropriate business strategies that can enhance its competitiveness. This research employs both qualitative and quantitative methods, combining interviews with internal stakeholders involved in digital lending operations and surveys capturing customer perceptions. Secondary data were obtained from internal company reports and relevant literature. The findings indicate that the slow progress in digital multipurpose loan implementation is primarily driven by the company's deeply rooted conventional culture, low prioritization of digital initiatives, limited investment in technology, and weak promotional strategies. Additionally, intense market competition and the growing threat of substitute products offering faster and more convenient digital loan services exacerbate the challenge. To address these issues, strategic organizational restructuring aligned with a differentiation strategy is recommended, supported by targeted digital product development and improved human resource capabilities across divisions. Digital transformation is thus positioned not only as a technological shift but also as a key economic driver in strengthening PT. XYZ Finance’s strategy execution in the evolving loan market.